2022
DOI: 10.3390/children9111688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Pain in Fetuses, Neonates and Children

Abstract: The perception of pain is individual and differs between children and adults. The structures required to feel pain are developed at 24 weeks of gestation. However, pain assessment is complicated, especially in neonates, infants and preschool-age children. Clinical scales adapted to age are the most used methods for assessing and monitoring the degree of pain in children. They evaluate several behavioral and/or physiological parameters related to pain. Some monitors detect the physiological changes that occur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…These reports showing the negative impacts of sucrose and other sweet-tasting solutions given during infancy, particularly in preterm infants, on lessening procedural pain in the neonatal intensive care unit ( Mencía et al, 2022 ; Fulkoski et al, 2023 ) should be given greater consideration, and more studies are required to explore this negative effect. In addition, more research is needed to explore the mechanisms associated with the long-term harmful effects of pain, as well as the efficacy and safety of using sucrose in neonatal intensive care units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports showing the negative impacts of sucrose and other sweet-tasting solutions given during infancy, particularly in preterm infants, on lessening procedural pain in the neonatal intensive care unit ( Mencía et al, 2022 ; Fulkoski et al, 2023 ) should be given greater consideration, and more studies are required to explore this negative effect. In addition, more research is needed to explore the mechanisms associated with the long-term harmful effects of pain, as well as the efficacy and safety of using sucrose in neonatal intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…The management of neonatal pain is a critical health issue that is increasingly recognized by clinicians and researchers ( Hall and Anand, 2014 ; Carter and Brunkhorst, 2017 ; Shah and Siu, 2019 ; Carbajal, 2020 ; Mencía et al, 2022 ). However, the use of classical pain medications has some adverse effects in both the short and long term, thereby making their use controversial ( Bastaki et al, 2018 ; Shah and Siu, 201; Kinoshita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperatively, pain intensity was assessed by FLACC pain score 1 (Face, Leg, Activity, Cry, Consolability) at 2, 4, 6, 8, 12, 18, and 24 h, as follows (0 = No pain; 1–2 = mild pain; 3–5 = moderate pain; 6–8 = severe pain; 9–10 = extreme–maximum pain) when FLACC score was ≥4, rescue analgesia in the form of intravenous acetaminophen (perfalgan ® ) 15mg/kg was given, if the patient was still in pain additionally diclofenac 25 mg suppository was given. The overall quantities of consumed analgesia and duration for the initial request of analgesia in the first 24 h postoperatively were measured and documented.…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric pain management is still misunderstood and not well managed especially in neonates and infants, due to the misconception that they are not able to sense pain as adults. 1 This induces negative consequences, including a variety of autonomic, metabolic, hormonal, immunological or inflammatory, and neurobehavioral effects. 2 Combining general anesthesia with regional or nerve blocks for this population enables a smooth intraoperative course, reduced need for general anesthetics, avoiding hazardous side effects from parenteral administration of narcotics during surgery, reduced stress response, pain-free awakening, and, most importantly, perfect postoperative pain control.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, of interest include those that were carried out in children with dental or tooth-extraction-related pain [ 65 , 66 , 67 , 68 ], in those with migraine [ 69 ], in those with pharyngotonsillitis [ 70 ], and in those with postoperative tonsillectomy pain [ 71 , 72 , 73 ]. In all these instances, the analgesic effect of PC was significantly greater than that of a placebo and noninferior to that of NSAIDs, including ibuprofen and ketoprofen [ 74 ]. Moreover, clinical studies have shown that using PC, even at low analgesic doses, allows for a significant reduction in the simultaneous administration of other non-opioid or opioid drugs, thus reducing the risk of drug-related adverse events [ 75 ].…”
Section: Treatment Of Pediatric Painmentioning
confidence: 99%